Cladistic analysis of Zethini (Hymenoptera, Vespidae, Eumeninae) with emphasis on the subgeneric classification of Zethus Fabricius, 1804 - Lopes, Rogério Botion (2018)
Vespidae is a cosmopolitan family with over 5.000 species, which are organized into six extant subfamilies. Eumeninae is the most diverse with over 3.700 species and subdivided into three tribes: Eumenini, Odynerini and Zethini. This classification was proposed based on morphological cladistic analysis, but molecular analyses disagree with some of the proposed groups. Despite what dataset was used, Zethini has always been poorly sampled, what may influence the results in a way that the monophyly of the tribe and intergeneric relationships become questionable. Thus, a cladistic analysis of the group was carried in order to verify the monophyly of the tribe, which genera are included in the tribe and the relationship between them. The study involved 105 Zethini terminals and 201 morphological characters, which were submitted to implied weighting through a newly created script. A single obtained tree recovered Zethini as monophyletic comprised by the following genera: Raphiglossoides, Elisella, Psiliglossa, Raphiglossa, Protodiscoelius, Discoelius, Argentozethus, Australozethus, Macrocalymma, Pachycoelius, Deuterodiscoelius, Calligaster, Elimus, Paramischocyttarus, Zethus, Ctenochilus and Ischocoelia. However, Pachycoelius and Deuterodiscoelius were paraphyletic one in relation to the other, leading to the synonymy of the former under the latter. Zethus was also paraphyletic, but regarding Ctenochilus and Ischnocoelia, which were included in Zethus as subgenera. Besides the forementioned, Zethus is now comprised of other eight subgenera: Z. (Madecazethus), Z. (Zethastrum), Z. (Wettsteinius), Z. (Zethusculus), Z. (Zethoides), Z. (Parazethus), Z. (Didymogaster) and Z. (Zethus).